The effect of the die material used in the indirect technique on the fracture resistance of a restored molar - Paulo Victor de Moura COSTA; Amanda Alves de OLIVEIRA; Vitória Ariella Silveira e SILVA; Érica Miranda de TORRES; Maria Alves Garcia Santos SILVA; Crisnicaw VERÍSSIMO (Sociedade Brasileira de Pesquisa Odontológica, 2023)
Abstract The aim of this study was to evaluate the effect of different die materials used in the indirect resin composite restorative technique on the fracture resistance and failure mode of restored molars and compare it with the direct resin composite restorative technique. Two flexible die silicone materials for dental models (Die Silicone - Voco and Scan die - Yller) and a type IV dental stone material (Fujirock EP - GC) were evaluated. Sixty third molars were selected and divided into four groups: indirect resin composite restoration - Die silicone (IRCR-DS); indirect resin composite restoration - Scan die (IRCR-SD); indirect resin composite restoration - Fujirock EP (IRCR-FR), and direct resin composite restoration (DRCR). Class II MOD cavities were prepared with 5 mm of buccolingual width and depth. The specimens were restored and subjected to an axial compression load until fracture, and the data were analyzed by one-way ANOVA and Tukey's HSD test (α=.05). The fracture mode was classified into restorable and unrestorable fractures. Fracture resistance values were influenced by the die material used for the IRCR fabrication and by the restorative technique (p<.001). Fracture resistance mean values and standard deviation were: IRCR-DS: 1835.5 ± 324.0 A; IRCR-SD: 1732.5 ± 384.1 AB; IRCR-FR: 1419.3 ± 318.8 BC; and DRCR: 1100.6 ± 224.9 C. Restorable fracture was more prevalent. IRCR with flexible die casts promoted higher fracture resistance and lower prevalence of unrestorable fractures.